Respuesta :
Get x on one side of the equation and everything else on the other side.
On the left-hand side, we have some like terms that we can combine.
4x + 7 - 9 = -14
4x - 2 = -14
Now reverse the operations done to x by using the inverse of those operations.
4x - 2 = -14
4x = -12 <-- Add 2 to both sides
x = -3
So, x is equal to -3.
On the left-hand side, we have some like terms that we can combine.
4x + 7 - 9 = -14
4x - 2 = -14
Now reverse the operations done to x by using the inverse of those operations.
4x - 2 = -14
4x = -12 <-- Add 2 to both sides
x = -3
So, x is equal to -3.